Pengembangan LKPD berbasis STEAM untuk Meningkatkan Keterampilan Proses Sains Peserta Didik Pada Materi Tumbuhan Kelas IV Sekolah Dasar - Toyibah Toyibah; Yessy Yanita Sari; Irdalisa Irdalisa (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
The student worksheet, also known as LKPD, is a crucial element in the educational process inside schools. Nevertheless, several LKPDS fail to satisfy the requirements of being feasible, valid, and successful in enhancing the abilities of science process learners. Furthermore, the absence of stimuli in the LKPD to foster critical thinking among learners is a pressing issue that requires attention. The objective of this project is to create a Science, Technology, Engineering, Arts, and Mathematics (STEAM) focused Learning Kit and Performance Dashboard (LKPD) that may enhance the scientific process and creative abilities of fourth-grade children in primary school, specifically in relation to plant matter. The study employed the ADDIE Development paradigm, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The findings demonstrated that the STEAM-oriented LKPD created had a positive impact on enhancing the science process abilities and fostering creativity among fourth-grade pupils in relation to plant matter. Furthermore, the enthusiasm for acquiring knowledge and the level of scientific literacy also exert a beneficial impact on the science process abilities of individuals. Teachers and learners also evaluate the LKPD for its viability and practicality